Students and Lecturers’ Perception Toward Powerpoint as an Aid of Accounting Textbooks - Nurlailia, W; ., Sulastri (KnE Social Sciences, 2018)
This descriptive comparative research is used to know the perception of students and lecturers toward the use of PowerPoint as an aid of accounting textbooks. The data were collected through questionnaires given to students and lecturers of State University of Malang and Brawijaya University which were randomly taken as many as 202 students and 6 lecturers. The questionnaire contains the principles of multimedia learning design in designing a PowerPoint, and students and lecturers were asked to fill in the forms using a Likert scale. The collected data will be analyzed using proportion model (percentages) in order to know the majority of students and lecturers’ perception. The t-test is also used to investigate whether there exists any difference between students and lecturers’ perception. By knowing the perception of students and lecturers toward PowerPoint as an aid of accounting textbooks, it is expected that lecturers will not directly input materials from Kieso’s Intermediate Accounting IFRS into learning and teaching activities. Keywords: PowerPoint, Cognitive Load Theory, Perception, Principles of Multimedia Learning Design